A casa brasileira do século XIX e seus desdobramentos na produção residencial de Belo Horizonte: influência dos antecedentes coloniais e o papel do neoclassicismo e do ecletismo - Suellen Dayse Versiani dos Santos (2011)
The residential architectural production of a society constitutes an important element of their culture. This space dialogues with both the natural conditions, such as weather and availability of materials, and with aspects related to customs and way of life. In this sense, a social groups houses represent an area of great importance, because they allow us to observe the influence of several factors in individuals housings shaping, be these factors related to changes or to traditions preservation.Given this complexity that revolves around the living space, the houses were chosen as this studys main object, which aims to investigate the influences of the changes undertaken by nineteenth century, especially those related to Eclecticism, in the homes production of Belo Horizontes firsts decades. For this purpose it was necessary to analyze the homes produced in Brazil in the nineteenth century, in order to ascertain which houses aspects have undergone transformations and whatwere the main agents of these changes. At the same time, to better understand the changes that occurred during this period, a study on Brazilian colonial homes was undertaken. These analysis were crucial for the identification of issues that ended up by instituting themselves as traditions relating to housing and peoples ways of life. The research, then, brings a study on Brazilian house, which pervades theproduction of the colonial period, of the nineteenth century and culminates with an analysis of residences built in the early decades of Minas Geraiss new capital (late nineteenth and early twentieth century).